2018
DOI: 10.1111/jcmm.13964
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid induces apoptosis and suppresses metastasis in hepatocellular carcinoma cell lines in vitro and in vivo

Abstract: Hepatocellular carcinoma (HCC) is a high incidence and mortality malignant tumour globally. Betulinic acid (BA) is a pentacyclic triterpenoid with potential pro‐apoptotic activities which widely found in many plants. In this study, we determined the effects of BA on proliferation, apoptosis, invasion, and metastasis in HCC cell lines and on tumour growth and pulmonary metastasis in mice. The results suggested that BA could inhibit cell viability and proliferation of HCC cell lines including HepG2, LM3, and MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…BA has many pharmacological activities, including tumor suppression and anti‐inflammatory effects 29,30,44 . It has been showed to induce apoptosis and suppress metastasis in HCC cells and HepG2 xenograft mice 45 . Consistent with this, we demonstrated that BA inhibited tumor progression and invasion in orthotopic HCC mice.…”
Section: Discussionsupporting
confidence: 87%
“…BA has many pharmacological activities, including tumor suppression and anti‐inflammatory effects 29,30,44 . It has been showed to induce apoptosis and suppress metastasis in HCC cells and HepG2 xenograft mice 45 . Consistent with this, we demonstrated that BA inhibited tumor progression and invasion in orthotopic HCC mice.…”
Section: Discussionsupporting
confidence: 87%
“…The cells were treated with betulinic acid after the cells growth can be visible to the naked eye. After 24 h of treatment, cell colonies were fixed with formaldehyde and stained with crystal violet for counting [9].…”
Section: Colony Formation Assaymentioning
confidence: 99%
“…Formaldehyde and 0.5% crystal violet (Sigma) were then used to fix and stain the invaded cells in correct order. To ensure the accuracy of the counting, five random fields under a microscope were selected to calculate the number of invaded cells [9].…”
Section: Transwell Assaymentioning
confidence: 99%
“…Betulinic acid (BA), a naturally occurring pentacyclic triterpenoid in the bark of plane and birch trees, has been demonstrated to exert a variety of biological features. In addition to its anti-HIV [1], antiparasitic [2] and antiinflammatory [3] properties, BA shows anticancer activity in vitro and in vivo [4][5][6][7][8][9][10]. Its antitumor effects are mediated mainly by a CD95-and p53-independent induction of apoptosis [11].…”
Section: Introductionmentioning
confidence: 99%